A note comparing the apparent metabolisable energy of three oil sources and their combination in broiler chickens - Abdulla, Nazim Rasul; Loh, Teck Chwen; Akit, Henny; Sazili, Awis Qurni; Foo, Hooi Ling (Universiti Putra Malaysia Press, 2016)
Apparent metabolisable energy (AME) of palm oil (PO), soybean oil (SO), linseed oil (LO) and blend oil (BO) in a ratio of 4:1:1 were evaluated. A total of 75, 21-day-old birds were fed corn-soy basal diet and the four test diets containing different oil sources (PO, SO, LO and BO), that were developed by replacing 60 g/kg of the basal diet for eight days. Differences in the apparent metabolisable energy were found (P<0.05), with the higher values for broiler-fed BO. This study affirmed that BO increases AME of oil enriched with saturated fatty acid in poultry diets.